A Quantitative Ethnobotanical Study of Plants Used by the Locals in Camiguin Island, Calayan, Cagayan, Philippines - Rudolph Valentino A. Docot; Amritveer Singh Sohal; Carylle G. Dela Cruz; Kaye Allison P. Fontillas; Marc Allan G. Rodriguez; George Emmanuel M. Trillana; Mark Lloyd Granaderos Dapar (Journal of Tropical Life Science, 2022)
Traditional knowledge concerning plant utilization in the Philippines is common but is largely underappreciated. Assessment of plant resources by groups of people helps promote valorization of cultural heritage. However, particularly in the Camiguin Island of the North, Cagayan (not to be confused with the island province of Camiguin in Mindanao), the use of terrestrial plants remains unknown. As a response, this study aims to identify terrestrial plants in the island which have ethnobotanical importance through survey interview. The data collected were then analyzed using quantitative ethnobotanical methods. A total of 70 species belonging to 44 plant families were surveyed from the 33 informants. The statistical analysis showed a significant difference between male and female informants in terms of ethnobotanical knowledge. Lamiaceae was the most represented plant family with five species recorded. Leaves were the most used plant part (51%), congruent to previous ethnobotanical studies in the Philippines. Most medicinal preparations were done through decoctions (41.03%). Much of the medicinal plants surveyed were administered through topical medication (54.90%), and this is because the occupation of the people of Camiguin island mostly involves heavy physical activities. Thus, the probability of being wounded in the area is very high. It was found that Vitex negundo was the most used plant in Camiguin island with the used value of 0.15. Furthermore, five ailment/disease categories obtained a 100% fidelity level. This result indicates that the plants used for that disease category are considered the most preferred species. Respiratory diseases obtained the highest FIC value of 0.40, indicating species within that category are the best candidates to search for bioactive compounds. This documentation provides the first checklist of useful plants in Camiguin island and will serve as a basis for future ethnobotanical studies in the Philippines.